1992
DOI: 10.1007/bf02191956
|View full text |Cite
|
Sign up to set email alerts
|

Hypofrontality on topographic EEG in schizophrenia

Abstract: Topographic EEG was performed in 17 DSM-III-R schizophrenic patients and in 15 sex- and age-matched healthy controls. Eleven patients were first-onset (neuroleptic naive) schizophrenics. EEG band power was compared with psychopathology, neuropsychology and neurological soft signs. The EEG was recorded at 14 topographic locations monopolarly and movements of the eye and of the lid were monitored by two bipolar electro-oculogram (EOG) derivations, one vertical and one horizontal. A multivariate correction of EOG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
1
3

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(34 citation statements)
references
References 29 publications
4
24
1
3
Order By: Relevance
“…This is coherent with previous results displaying elevated power in the faster bands in schizophrenia [15]. Fast oscillations may contribute to forming local neuronal assemblies [38], which, according to our results, may suggest a relative deficit in the integration of activities from distant regions in schizophrenia.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This is coherent with previous results displaying elevated power in the faster bands in schizophrenia [15]. Fast oscillations may contribute to forming local neuronal assemblies [38], which, according to our results, may suggest a relative deficit in the integration of activities from distant regions in schizophrenia.…”
Section: Discussionsupporting
confidence: 81%
“…Higher gamma noise power (corresponding to power unrelated to task performance) has been reported during a P300 task in schizophrenia [14]. Moreover, higher mean power in the faster bands has been reported in this illness [15], as well as a positive correlation between positive symptoms and gamma power responses [16]. It has been suggested that this association may reflect a cortical hyperexcitability that possibly disturbs the conscious experience [11].…”
Section: Introductionmentioning
confidence: 99%
“…A predominance of delta and theta activity has been reported over posterior scalp sites (e.g., Harris et al 1997;Ulrich and Otto 1984;Westphal et al 1990), but also at central (Karson et al 1987(Karson et al , 1988, left lateral (Schellenberg et al 1989), frontal (Gattaz et al 1992), or frontotemporal (Serafetinides 1984) electrodes. Some studies emphasize that the distribution of slow wave activity is generally diffuse or variable (Elbert et al 1992;Fenton et al 1980;Galderisi et al 1991;Macmahon and Walter 1938).…”
Section: Introductionmentioning
confidence: 97%
“…Negative correlation between delta rhythm and cortical metabolism was also established [26], as well as positive correlation between delta activity and negative symptoms [27].…”
Section: Discussionmentioning
confidence: 99%